2021
DOI: 10.1159/000516369
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Atrial Fibrillation on the Long-Term Mortality of Patients with Acute Coronary Syndrome: The TACOS Study

Abstract: <b><i>Introduction:</i></b> Atrial fibrillation (AF) is a frequent finding in acute coronary syndrome (ACS), but there is conflicting scientific evidence regarding its long-term impact on patient outcome. The aim of this study was to survey and compare the ≥10-year mortality of ACS patients with sinus rhythm (SR) and AF. <b><i>Methods:</i></b> Patients were divided into 2 groups based on rhythm in their 12-lead ECGs: (1) SR (<i>n</i> = 788) at hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…We found that AF is a surrogate marker of disease in patients with MI rather than an independent risk factor. This was in contrast to previous studies [11][12][13][14][15][16][17], and our study demonstrated this over a longer period…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found that AF is a surrogate marker of disease in patients with MI rather than an independent risk factor. This was in contrast to previous studies [11][12][13][14][15][16][17], and our study demonstrated this over a longer period…”
Section: Discussioncontrasting
confidence: 99%
“…The reported prevalence of 2 of 13 concomitant AF in patients following acute MI varies widely, with reported rates ranging between 6 and 21% [7,8]. Previous studies have identified AF as an independent risk factor both for MI [7][8][9][10] and for mortality after MI [11][12][13][14][15][16][17]. However, it is unclear whether this is due to a causal effect of AF or whether the observed effect is a result of AF acting as a surrogate marker for other comorbidities that influence the outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a need for early identification of high-risk patients who would benefit from treatment with long-term mortality outcomes. 60,61 Our review found that acute stroke was among the most common nonfatal MACE in patients hospitalized with ACS. Although it was less common (3%) compared to other MACE found in this review, however, stroke could be associated with significant morbidity and mortality.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, there is a need for early identification of high-risk patients who would benefit from treatment with long-term mortality outcomes. 60 , 61 …”
Section: Discussionmentioning
confidence: 99%
“…However, some evidence suggests that rhythm control may be preferable for younger patients (under 70 years old), while rate control may be more suitable for older individuals with multiple comorbidities such as heart failure and hypertension [11]. Recent studies have reported benefits in achieving short-and long-term restoration of sinus rhythm [12,13]. For patients who remain symptomatic despite receiving adequate rate control therapy, cardioversion (CV) is the preferred approach [8,9].…”
Section: Introductionmentioning
confidence: 99%